1999
DOI: 10.1111/j.1572-0241.1999.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Cyclosporin in Ulcerative Colitis: A Five-Year Experience

Abstract: CSA successfully allows most severe steroid resistant UC patients to retain their colons, and provides time for "elective" colectomy in others, especially if 6MP/aza are also given. Careful monitoring for side effects, including PCP prophylaxis, should be part of the treatment protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
184
1
16

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(212 citation statements)
references
References 5 publications
11
184
1
16
Order By: Relevance
“…Recently, several studies have reported a dramatic improvement with intravenous cyclosporine in patients with severe refractory UC [9, 16, 17]. However, reported experience with cyclosporine in pregnant women with UC is limited to one case report [18], and data from pregnancies in transplant recipients treated with cyclosporine suggest a high incidence of prematurity and low birth weight [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported a dramatic improvement with intravenous cyclosporine in patients with severe refractory UC [9, 16, 17]. However, reported experience with cyclosporine in pregnant women with UC is limited to one case report [18], and data from pregnancies in transplant recipients treated with cyclosporine suggest a high incidence of prematurity and low birth weight [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, most of the studies mentioned above have relied on corticosteroids to induce an initial remission. For patients who are refractory or intolerant of high-dose corticosteroids, the purine analogues have proved successful in maintaining a remission induced by cyclosporine [547][548][549] or tacrolimus therapy [550,551].…”
Section: Azathioprine and 6-mercaptopurine In Ulcerative Colitismentioning
confidence: 99%
“…One of the main advantages of cyclosporine is the rapid onset of response (typically within a few days), even in the most severely ill patients. Used mostly for corticosteroid-refractory ulcerative colitis, cyclosporine is typically added on to the corticosteroids as a continuous intravenous infusion at 2-4 mg/kg/day, with dose titration to achieve whole blood adjusted radioimmunoassay or high-performance liquid chromatography levels of 250-400 ng/mL [111,463,547,587,588]. Dose adjustments are often necessary because of side effects.…”
Section: Cyclosporine and Tacrolimusmentioning
confidence: 99%
See 1 more Smart Citation
“…After the initial placebo-controlled trial was reported [26], cyclosporine has emerged as a potent rescue therapy for patients presenting with steroid-resistant severely active UC. Subsequent retrospective studies have also shown response rates of around 80% [27, 28]. In practice, 2–4 mg/kg/day of cyclosporine is given intravenously as a 24-hour continuous infusion.…”
Section: Currently Available Therapies For Ucmentioning
confidence: 99%